2017
DOI: 10.13057/biodiv/d180350
|View full text |Cite
|
Sign up to set email alerts
|

Iron (II) and other heavy-metal tolerance in bacteria isolated from rock varnish in the arid region of Al-Jafer Basin, Jordan

Abstract: Abstract. Alnaimat S, Shattal SA, Althunibat O, Alsbou E, Amasha R. 2017. Iron (II) and other heavy-metal tolerance in bacteria isolated from rock varnish in the arid region of Al-Jafer Basin, Jordan. Biodiversitas 18: 1250-1257. This study deals with enumeration, identification and molecular characterization of bacterial species tolerant of iron (II) and other heavy metals that isolated from rock varnish collected from the arid region of Al-Jafer Basin, Jordan. Based on conventional culture-dependent methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A previous study demonstrated that Bacillus sp. resist Fe 2+ with MIC of 550 mg/L [53]. Other researchers also reported that Bacillus megaterium is resistant to Fe at MIC of 583.33 μg/mL [36].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that Bacillus sp. resist Fe 2+ with MIC of 550 mg/L [53]. Other researchers also reported that Bacillus megaterium is resistant to Fe at MIC of 583.33 μg/mL [36].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, measurement of the MIC and MBC of lead nitrate on the isolated bacteria showed that the genus Brevibacterium was highly resistant to lead (MIC = MBC = 39.74 mg ml −1 ). Alnaimat demonstrated that Brevibacterium and five other bacteria exhibited a high degree of tolerance to iron (II) and other heavy metals with the minimum inhibitory concentration of 550–600 mg l −1 to iron, and 500–550 mg l −1 to lead, in solid media (Alnaimat, 2017). Also, Elahi and Rehman by determining the MIC of several types of metals including lead, found that Brevibacterium iodinum was capable for tolerating lead with the concentration of 9 mM (Elahi & Rehman, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results revealed taxa associated with survival under extreme conditions such as salinity (e.g., Halococcus , Kocuria , Salinimicrobium , Pontibacter , Halobacterium , Marinobacter , and Halomarina ), UV radiation (e.g., Thuepera , Deinococcus , Coccomyxa , Rubrobacter , Chroococcidiopsis , Spirosoma , Scytonema , Blastococcus , and Modestobacter ), acidic conditions (e.g., Apatococcus , Acidobacteriaceae , Beijerinciaceae and Methylocystaceae ), alkaline conditions (e.g., Spirosoma , Rubellimicrobium and Truepera ) and low water availability (e.g., Chroococcidiopsis , Knufia , Leptolyngbya , Sarcinomyces , Rubrobacter , Capnobotryella , and Scytonema ) [17,35,40,41,42]. Other genera indicated the capacity to cycle nitrogen (e.g., Thiobacillus , Malikia , Ochrobactrum , Nitrososphaera , Nitrospira , Novosphingobium , and Nitrobacter ), cycle sulfur (e.g., Thioclava , Thiobacillus , Rhodovulum , and Desulfuromonas ), autotrophically fix carbon (e.g., Chroococcidiopsis , Leptolyngbya , Nostoc , Trebouxiophyceae , Phormidium , Aurantiamonas , Thiobacillus , Thioclava , Rhodobacter , and Acidimicrobium ), utilize minerals such as iron and manganese (e.g., Aurantimonas , Acidimicrobium , and Ferrimicrobium ) and bioprecipitate minerals (e.g., Bacillus , Stenotrophomonas , Pseudomonas , and Crosiella ) [10,29,30,35,42].…”
Section: Community Assembly At the Mineral-air Interfacementioning
confidence: 99%